New optical techniques to improve the visibility of graphene on multiple substrates - Gonçalves, Hugo (2011)
Optical microscopy as a means to identify graphene is hampered by the low absorptivity of its monolayers and few-layer structures. However for many of the upcoming applications for graphene, it is essential to develop techniques to readily deliver images of graphene based structures. We report on two novel techniques and additionally on a well-known, but modified technique for the identification of graphene. All of the described methods employ standard optical reflection and transmission microsocopy and can be readily adapted in most laboratories. One of the novel techniques is based on the enhancement of the optical contrast by refractive index matching using oil immersion microscopy. The second technique, microdroplet condensation, exploits the hydrophobicity difference between the carbonic sheets and almost any arbitrary substrate. The third technique is a modification of the already well known technique to enhance the visibility contrast of graphene using interferometric effects by employing a Si wafer coated with a dielectric of specific thickness.